Cockroach (Blattodea, Blaberoidea) fauna of the Maltese Islands, with descriptions of two new species - Bohn, Horst; Sciberras, Arnold (Zootaxa, 2021)
Cockroach (Blattodea, Blaberoidea) fauna of the Maltese Islands. Hitherto seven species of cockroaches were known from the Maltese Archipelago (Schembri 1980): four of them are synanthropic species introduced by man: Blatta orientalis, Blattella germanica, Periplaneta americana and Supella longipalpa; the remaining three are indigenous species: Ectobius kraussianus, Loboptera decipiens and Polyphaga aegyptiaca. The earlier reports almost exclusively concern the largest island Malta; only one report (L. decipiens) applies to the islet Comino. Faunistic part. By recent collectings of the authors (mainly A.S.) including also the smaller islands Gozo, Comino and some rock islets (Cominotto, Filfla, Fungus Rock, Large Blue Lagoon Rock, Pigean Rock) the known distribution of the species could be largely widened; two further obviously indigenous species were found, both new to science and presumably endemic to Malta: Ectobius melitensis, sp. nov. (Ectobiidae, Ectobiinae) and Heterogamisca jeffreyana, sp. nov. (Corydiidae, Corydiinae). E. kraussianus presumably has to be eliminated from the list of Maltese cockroaches; the older report most likely concerns a misidentified E. melitensis. During the last years the number of introduced species was strongly increased (1) by escapees of species cultivated for the nourishment of amphibia and reptilia, as are Blaptica dubia, Gromphadorhina sp., Nauphoeta cinerea, Periplaneta fuliginosa, Shelfordella lateralis and Symploce pallens, and (2) by species presumably imported with gardening materials: Pycnoscelus surinamensis and Phoetalia pallida. The mentioned species have repeatedly been found in human buildings and adjacent gardens of a number of settlements, mostly in the surroundings of the capital Valetta. They seem to be well established there; part of them has even been observed in the wild. The newly introduced species are in spite of their successful establishment and reproduction in Malta not considered as a danger for the indigenous species: The great differences in the requirements between the two groups most likely exclude competition between them. Three species, Ectobius vittiventris, Henschoutedenis flexivitta, and Periplaneta australasiae, have only occasionally been found and can, therefore, scarcely be considered as members of the Maltese fauna; the latter also applies to species of the genus Panchlora which were repeatedly observed on fruit markets at freshly imported bananas, but never found outside, neither in the Maltese banana plantations. Taxonomic part. The new species are described and compared with their closest relatives, colouration and characteristic structures are shown in several figures. Ectobius melitensis belongs to the kraussianus-species group of Ectobius known from Sicily and surrounding islands (Ustica, Aeolian Islands, Ponza), but with one species also reaching Albania; the nearest relatives of Heterogamisca jeffreyana are occurring on the Iberian Peninsula and North Africa (Morocco, Algeria, Tunisia).